The influence of brand trust, brand preference and perceived value on purchase intention in local skincare products - Dionita Sabrina Destiya; Albari, Albari (Cita konsultindo, 2024)
This study aims to examine the influence of brand trust, perceived value, and brand preference on purchase intention, with a case study on local skincare brands available on Sociolla. The sample size used was 186, selected through a non-probability sampling technique, specifically convenience sampling. Data analysis was conducted using the SEM technique with the help of AMOS v22 software. The results of the study indicate that brand trust and perceived value have a positive influence on brand preference. Additionally, brand trust, perceived value, and brand preference positively impact purchase intention.